Power, inequality, and water governance: The role of third party involvement in water-related conflict and cooperation - Gomez, Helle; Ravnborg, Helle Munk (International Food Policy Research Institute, 2011)
Water governance reforms are underway in many parts of the developing world. They address the principles, institutions, and legal and administrative practices through which decisions are made on the development, allocation, and conditions of use of water resources at all levels of society. As such, water governance--and efforts to reform it--is shaped by and helps to shape the way in which decisions are taken and authority is exercised in fields that extent well beyond water. Based upon research conducted in Condega district, Nicaragua, this paper argues that community-specific power constellations may lead to the existence of radically different water governance regimes among neighboring communities, despite these communities sharing the same national and district-level water policy and associated legal and administrative framework. Moreover, the involvement of community-external third parties to mediate in situations where peoples legitimate access to water is challenged provides a promising avenue towards ensuring more equitable water governance. However, institutions potentially serving as such community-external third parties are often too poorly staffed or their staff too poorly supported--technically, economically, and institutionally--to attend to calls for support. Furthermore, in contexts characterized by economic, social, and political inequality, the community-specific power constellations may limit opportunities available to different segments of the rural population for calling upon community-external third parties in cases when their legitimate access to water is hampered by the locally powerful. Ensuring that all rural citizens enjoy equal opportunities for calling upon third party institutions constitutes a challenge to local water governance